(untitled) (The Geographic Base, 2023)
This paper investigates the spatial micro-econometrics of businesses within Kirtipur Municipality. Primary data was collected through field surveys, and observations, supplemented by secondary sources. Findings revealed an increasing trend in firm establishments, particularly along roadsides, with wards 9 and 10 hosting more firms than wards 7 and 8. Proximity to road access positively correlated with establishment numbers. Ward 6 showed significant establishment presence due to factors like road accessibility and raw material availability. The study’s modeling analysis indicated a relation between the distance from main roads and the likelihood of new firm establishment. Positive spatial externalities were observed, which implies that the beneficial effects that arise from the geographical proximity or spatial arrangement of economic activities, individuals, or firms – cause with new firms to cluster around existing ones. Manufacturing industries experienced the highest growth rate at 366.7%, while sectors like petrol pumps and schools exhibited more modest growth rates of 27.3%. This research provides valuable insights into the spatial economic dynamics of Kirtipur Municipality, including firm establishment, growth patterns, and the influence of spatial factors which refers to geographical location, distribution, and arrangement of economic resources, firms, and individuals, on economic activities .